Analysis and optimization of coupling to external cavities in feedback experiments with vertical-cavity surface-emitting lasers - Jentsch, Karl Friedrich; Sondermann, Markus; Ackemann, Thorsten (Optics Communications, 2008)
The feedback strength is a crucial parameter for feedback experiments using semiconductor lasers. In this article, the coupling efficiency of the field of vertical-cavity surface-emitting lasers (VCSELs) to external cavities containing one collimating lens has been analyzed in detail using ABCD-matrix methods. It is found that for a given set of parameters there are two distinct, experimentally realizable positions of the collimating lens which allow for optimal coupling, if the cavity length is sufficiently small. The predictions are verified in experiments using single-transverse-mode VCSELs. The obtained coupling efficiencies exceed 70%. © 2007 Elsevier B.V. All rights reserved.
Keywords: Coupling efficiency; Feedback; Vertical-cavity surface-emitting lasers